Superalloys 2004 (Tenth International Symposium) 2004
DOI: 10.7449/2004/superalloys_2004_951_958
|View full text |Cite
|
Sign up to set email alerts
|

The Sensitivity of Investment Casting Simulations to the Accuracy of Thermophysical Property Values

Abstract: In this study, the importance of the accuracy of the thermophysical property to a simulation of an investment cast directionally solidified nickel-based superalloy turbine blade was investigated. CMSX-4 was chosen as the base alloy. The effect of the thermophysical properties on the thermal field and solidification microstructure was studied using a coupled macromesoscale model. Relevant thermophysical properties examined include density, specific heat (enthalpy) and thermal conductivity in both the liquid and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Lee and coworkers investigated the sensitivity of investment casting simulations to the accuracy of thermo-physical properties. [17] They found that the temperature prediction and thermal gradient in the liquid are the most sensitive to the accuracy of the input values used for density and thermal conductivity in the solid. Thermal conductivity in the liquid, specific heat, and density have similar levels of influence on solidification time; increasing their values increases the local solidification time.…”
Section: Thermo-physical Properties Calculationmentioning
confidence: 99%
See 1 more Smart Citation
“…Lee and coworkers investigated the sensitivity of investment casting simulations to the accuracy of thermo-physical properties. [17] They found that the temperature prediction and thermal gradient in the liquid are the most sensitive to the accuracy of the input values used for density and thermal conductivity in the solid. Thermal conductivity in the liquid, specific heat, and density have similar levels of influence on solidification time; increasing their values increases the local solidification time.…”
Section: Thermo-physical Properties Calculationmentioning
confidence: 99%
“…Among all the thermo-physical data, the temperature dependent density is critical for the accurate simulation of solidification microstructure and defect formation. [17] A database has been developed containing molar volume and thermal volume coefficients of expansion of liquid, solid solution elements, and intermetallic phases. This is linked to the thermodynamic calculations mentioned above.…”
Section: Densitymentioning
confidence: 99%
“…Deviations in the accuracy of forecasts are most commonly caused by material data mismatches in the conditions of production in the foundry. The problem of the sensitivity of the model to the errors of coefficients has been developed, among others, in [10][11][12]. The creators of casting simulation codes, as a principle (customary) do not take responsibility for the quality of the parameters contained in the database and at the same time they suggest modifications of material data provided there and supplementing the database with material parameters and the boundary conditions corresponding to the material and assortment conditions of casting in the particular foundry.…”
Section: The Place Of Simulation Codes In the Foundry Industrymentioning
confidence: 99%
“…For example, Sahai and Overfelt [34] reported a HTC in the range 50-5,000 W m −2 K −1 for IN-718 Ni-based superalloy. The HTC at the mold-wrap, moldenclosure, and wrap-enclosure interfaces have less influence on the final result of the thermal model as shown by Yuang et al [35]. Thus, it was assumed that they were constant with temperature and time, and the data from the ProCAST database were used ( Table 2).…”
Section: Thermal Model Development Of the Thermal Modelmentioning
confidence: 99%